Understanding Studentsâ Cyberslacking Behaviour in e-Learning Environments: Is Student Engagement the Key? - Koay, K.Y. (Taylor and Francis Ltd., 2022)
Many universities have slowly moved to online teaching due to the COVID-19 pandemic. Without the physical presence of instructors, students can easily engage in cyberslacking behaviour during online classes. Hence, the purpose of this research is to examine the association of student engagement with studentsâ cyberslacking behaviour during online classes. Both student engagement and cyberslacking are multidimensional constructs. Partial least square structural equation modelling (PLS-SEM) is used to analyse data from 194 university students using a survey method. The results reveal that psychological motivation, cognitive problem-solving, and interactions with instructors do not have a significant association with cyberslacking behaviour. On the other hand, peer collaboration, community support, and learning management are found to have different associations with different dimensions of cyberslacking behaviour. Learning management is identified as the most robust predictor of cyberslacking behaviour. This research fills the research gaps by investigating the associations of various dimensions of student engagement with different dimensions of studentsâ cyberslacking behaviour in the context of e-learning environments. Â© 2022 Taylor & Francis Group, LLC.